2014
DOI: 10.1039/c4ta03731f
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional heterostructures of V2O5 and reduced graphene oxide as electrodes for high energy density asymmetric supercapacitors

Abstract: The 2D layered heterostructures of V2O5 nanosheets and reduced graphene oxide show high conductivity and superior asymmetric supercapacitor properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
75
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 202 publications
(80 citation statements)
references
References 50 publications
(37 reference statements)
4
75
1
Order By: Relevance
“…[1][2][3][4] Among layered oxides, vanadium oxide is one of the most extensively studied binary oxides due to its rich variety of vanadium/oxygen stoichiometries and characteristic properties of the individual phases (such as V 2 O 5 , VO 2 , V 2 O 3 , V 6 O 13 etc.). This has resulted in many studies targeting the use of vanadium oxide in various applications such as energy storage, 5,6 catalysis, 7 electrochromism, 8 sensing, 9 and spintronic devices. 10 In contrast, VO x thin films have also been reported recently for resistive switching performance by several groups.…”
mentioning
confidence: 99%
“…[1][2][3][4] Among layered oxides, vanadium oxide is one of the most extensively studied binary oxides due to its rich variety of vanadium/oxygen stoichiometries and characteristic properties of the individual phases (such as V 2 O 5 , VO 2 , V 2 O 3 , V 6 O 13 etc.). This has resulted in many studies targeting the use of vanadium oxide in various applications such as energy storage, 5,6 catalysis, 7 electrochromism, 8 sensing, 9 and spintronic devices. 10 In contrast, VO x thin films have also been reported recently for resistive switching performance by several groups.…”
mentioning
confidence: 99%
“…After carrying out hydrothermal treatment to wrap GO on V 2 O 5 resistance increased to 10 5 . On the other hand it was observed that after heat treatment, when GO was reduced to RGO, resistance drops by three orders of magnitude coming down to 10 2 [33,34]. The results of Cole-Cole-fit are reported in Table 1.…”
Section: Impedance Analysismentioning
confidence: 83%
“…[204] As discussed by the nanostructured LiCoO 2 , some of the 2D transition metal oxides or hydroxide nanosheets such as V 2 O 5 , VOPO 4 , NiO, TiO 2 (B), Co 3 O 4 , and nickel and cobalt hydroxide can show extrinsic intercalation pseudocapacitance driven by the fast intercalation through the tunnels or layers with the low activation energy for ion insertion. [206,207] Nagaraju et al [206] have reported the 2D layered heterostructured V 2 O 5 nanosheets/graphene composites with high Faradaic activity and applied as an asymmetric supercapacitor devices in an aqueous electrolyte (Figure 20a). [205] In a bulk orthorhombic phase, V 2 O 5 showed typical battery behavior of several voltage plateau profile.…”
Section: Transition Metal Oxide and Hydroxidesmentioning
confidence: 99%